Response distances of wild forest reindeer (Rangifer tarandus fennicus Lönnb.) and semi-domestic reindeer (R. t. tarandus L.) to direct provocation by a human on foot/snowshoes - Nieminen, Mauri (Rangifer, 2013)
The objective of the study was to examine response distances of wild forest reindeer (Rangifer tarandus fennicus Lönnb.) and semi-domestic reindeer (R. t. tarandus L.) in Finland and Norway to direct provocation by a human on foot/snowshoes in 5 areas and in 15 reindeer herding cooperatives during different seasons in 2010-12. There were no significant differences in mean herd size or in sight, alert, flight and closest response distances of wild forest reindeer in the Kuhmo and Suomenselkä areas. The encounter distance in wild forest reindeer was significantly (P< 0.005) longer than in semi-domestic reindeer in Finland and in Finnmark, Norway, and it increased with the group size. The sight and the alert distances in wild forest reindeer were significantly (P< 0.001) longer than in semi-domestic reindeer. In addition, the flight distance for wild forest reindeer (mean 192 m) was significantly (P< 0.001) and almost three times longer than in semi-domestic reindeer in Finland (mean 68 m). The closest mean distance was in wild forest reindeer 191m (range 100-320 m) but only 44 m (range 2-110 m) in semi-domestic reindeer (P< 0.001). The sight, alert, flight and closest response distances were slightly longer in Norwegian than in Finnish semi-domestic reindeer. However, these distances were significantly (P<0.005) longer in Pohjois-Salla (no supplementary feeding) than in other Finnish reindeer herding cooperatives and at the Kaamanen experimental station. The mean flight distance of reindeer in Pohjois-Salla was 115 m but only 65 m in other cooperatives (P< 0.001). The closest distance of semi-domestic reindeer in Pohjois-Salla (mean 105 m) was more than 2.5 times longer than in other reindeer herding cooperatives (mean 40 m). The mean sight, alert and flight distances in wild forest reindeer in autumn and winter were significantly longer (P<0.005) than in semi-domestic reindeer in Finland. However, during summer these distances in wild forest reindeer herds with young calves were significantly longer (P<0.005). The mean herd size of Finnish semi-domestic reindeer was almost the same in different seasons, but in wild forest reindeer it was slightly bigger during winter and spring and smaller during summer and autumn, only 7-23 reindeer. The mean encounter and sight distances in semi-domestic reindeer were significantly longer (P<0.005) in winter, but the mean alert and flight distances were almost the same in winter and summer and slightly longer than during other seasons. The results suggest that the supplementary feeding practice during winter may likely cause a reduction in flight distances in semi-domestic reindeer.